Perancangan Arsitektur Enterprise FMIPA UNTAN Menggunakan Kerangka Kerja TOGAF Berbasis SOA - Nurul Mutiah; Ferdy Febriyanto (JSINBIS (Jurnal Sistem Informasi Bisnis), 2022)
The research aims to develop an Enterprise Architecture from FMIPA UNTAN, this is based on the many individual information systems that have been developed by FMIPA UNTAN which are not integrated in data and technology. This situation results in overlapping data that can affect the effectiveness of decision making within the organization. The designed Enterprise Architecture implements the concept of service-oriented architecture in order to support the integration between the business layer and the organization's technology layer. To support the research, several concepts are used, such as TOGAF as a framework for developing Enterprise Architecture, Service Oriented Architecture as a supporter for integration of architectural layers, and Archimate and Business Process Modeling Notation as a modeling language used to create architectural artifacts. The stages of the research included problem identification, the Enterprise Architecture development process followed the stages of TOGAF ADM namely the preliminary phase, architectural vision, business architecture, information system architecture, technology architecture, and making an architecture implementation roadmap. The results of the development of Enterprise Architecture are architectural artifacts consisting of catalogs, matrices, and diagrams of business, information system, and technology architecture. Based on the design results, it is found that the Enterprise Service Bus concept in Service Oriented Architecture can be used to support application and data integration in organization, as well as the concept of service access can bridge the gap between the business layer and the technology layer.